Fiction readership of U.P. Institute of Library and Information Science students - Parman, Reyna M. (2006)
The study investigated the status of UPILIS students. It determined the frequency and recency of reading, purposes in reading, average number of fiction books read in a month, reasons for not reading, fiction preference (in terms of form, genre, language), source of fiction materials, site of reading, and means of selection.